2017
DOI: 10.1080/23311835.2017.1382061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of second-order hyperbolic telegraph equation via new cubic trigonometric B-splines approach

Abstract: This paper presents a new approach and methodology to solve the second order one dimensional hyperbolic telegraph equation with Dirichlet and Neumann boundary conditions using the cubic trigonometric B-spline collocation method. The usual finite difference scheme is used to discretize the time derivative. The cubic trigonometric B-spline basis functions are utilized as an interpolating function in the space dimension, with a weighted scheme. The scheme is shown to be unconditionally stable for a range of  va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The L 2 and L ∞ errors and CPU time in seconds is shown in Table 1. Numerical results are compared with the obtained results in [23] and [28]. It can be concluded that the numerical solutions obtained by our algorithm are good.…”
Section: Applicationsmentioning
confidence: 85%
See 2 more Smart Citations
“…The L 2 and L ∞ errors and CPU time in seconds is shown in Table 1. Numerical results are compared with the obtained results in [23] and [28]. It can be concluded that the numerical solutions obtained by our algorithm are good.…”
Section: Applicationsmentioning
confidence: 85%
“…Using the linear system (6.6) for m = 5 and N = 1000 with the initial data V 0 = (0.2373, 0.2273, −0.0124, −0.0023, 0.0001, 0) T , V0 = V0 = (0, 0, 0, 0, 0, 0) T , we compute the approximate solution u 5 (x, t). The efficiency of Algorithm 1 is measured using L 2 , L ∞ and root mean square errors with ∆t = 0.0001, h = 0.01 which are shown in Table 3.The numerical results are compared with the obtained results in [28,23]. It can be concluded that the numerical solutions obtained by our algorithm are good.…”
Section: Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…The Fourier analysis (Von-Neumann) stability [32] analysis technique is applied to investigate the stability of the proposed method. Such an approach has been used by many researchers like [23][24][25][26]32].…”
Section: Stability and Convergent Analysismentioning
confidence: 99%
“…The Fourier analysis (Von-Neumann) stability [32] analysis technique is applied to investigate the stability of the proposed method. Such an approach has been used by many researchers like [23][24][25][26]32]. Now consider that the make nonlinearity in the difference scheme is linear by taking ] = max ( such that Thus this shows that the scheme is stable.…”
Section: Stability and Convergent Analysismentioning
confidence: 99%